Introduction: Mobilising Resources for the Army and Navy in the Eighteenth-Century Spanish Empire: Comparative, Transnational and Imperial Dimensions. (9th December 2020) - Brandon, Pepijn; Ferri, Sergio Solbes; Valdez-Bubnov, Iván
Abstract : The subject of this special issue is the relationship between the material demands of warfare and the political and administrative development of the Spanish imperial system during the long eighteenth century. Its purpose is to provide a transnational and comparative perspective on the methods employed by the Spanish monarchy to mobilise resources for war, emphasising the international, imperial and inter-regional connections that underpinned Spain's military and naval efforts. These methods implied specific types of involvement between the crown and the regional productive elites and were directly related to the capacity of the latter to mobilise resources and administer production processes. They were varied, ranging from total state administration of capital, labour and productive processes to an almost complete and relatively independent involvement of the empire's entrepreneurial elites, in Europe, America and Asia. The introduction by the guest editors positions the four contributions to this special issue within the wider context of the historiography on the mobilisation of resources for war. In recent years, scholars in this field have started to shift their attention from a primary focus on the development of 'fiscal-military' and 'fiscal-naval' arrangements that provided the financial backbone of states' warring activities, to the wider economic and social networks involved in supplying, recruiting, building and maintaining armies and navies. As the introduction argues, these networks, underpinning the emergence of European national states, were always inherently transnational.